Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1371/journal.pone.0246109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of umbilical cord milking versus delayed cord clamping on preterm neonates in Kenya: A randomized controlled trial

Abstract: Background Delayed cord clamping (DCC) is a placental to new-born transfusion strategy recommended by obstetric and gynaecological societies. Though not widely adopted, umbilical cord milking (UCM) may achieve faster transfusion when DCC cannot be performed such as when a neonate requires resuscitation. Methods Pragmatic, two-arm, randomized clinical trial in which consenting women in spontaneous labour or provider-initiated delivery at 28 to less than 37 weeks at Kenyatta National Hospital in Nairobi, Kenya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Another research comparing UCM with DCC for preterm newborns found that neonatal Hb and Hct levels were similar. UCM and DCC are two ways of placental transfusion that are similar ( 40 ). UCM effectively accelerates placental transfusion at the moment of birth, with advantages comparable to DCC ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another research comparing UCM with DCC for preterm newborns found that neonatal Hb and Hct levels were similar. UCM and DCC are two ways of placental transfusion that are similar ( 40 ). UCM effectively accelerates placental transfusion at the moment of birth, with advantages comparable to DCC ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA flow is shown in online supplementary Figure 1. Of the included RCTs, 18 enrolled 2,253 newborns born at <34 weeks of gestation [25, 27-33, 36, 38, 41, 43-45, 47-50] and 9 enrolled 883 LPT newborns [24, 26, 34, 35, 37, 39, 40, 42, 46]. Intransitivity was assessed by comparing the characteristics of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 27 included RCTs, 7 had a low ROB [25, 26, 36, 38, 39, 42, 45]. While 6 RCTs had some concerns [27, 31, 33, 37, 40, 43], 14 had a high ROB [24, 28-30, 32, 34, 35, 41, 44-50].…”
Section: Resultsmentioning
confidence: 99%
“…The cord was then released at the placental end and allowed to refill with blood for a brief 1 to 3 seconds pause between each milking motion (12, 14, 18-24, 27, 29-36, 39-41, 42, 43, 45-49, 53, 58, 66, 69, 74, 76-78) . In general, the entire procedure was completed in not more than 30 s. After this, the umbilical cord was clamped and cut at 2-3 cm from the umbilicus and the infant taken to the warmer for routine newborn care (20,23,26,35,43,48,50,61,69,74,77) .…”
Section: Resultsmentioning
confidence: 99%